Closed-loop Process Control for Laser Patterning of Thin Film Strain Sensors. (2016) - Düsing, J.F.; Koch, J.; Suttmann, O.; Overmeyer, L.
Abstract: This work presents a laser based bridge balancing method for strain sensor circuits which are applied directly on component surfaces by means of thin film deposition and laser patterning. The balancing process is integrated in the patterning process and consists of iterative cycles of laser scanning and bridge measurement operations until a balanced bridge circuit is generated. It is shown that a balanced bridge circuit on the surface of a non-planar surface can be generated within few scan cycles, and thus, allows for short processing times and high-throughput manufacturing of integrated thin film strain sensors on the surface of mechanical components.